Development of Quality Criteria and Proposed Specification Limits for Moringa Leaf Powder Through an Integrated Stakeholder and Evidence-Based Approach - Windri Widyaningsih; Mulyorini Rahayuningsih; Muslich (Jurnal Penelitian Pendidikan IPA, 2026)
The absence of quality standards for moringa leaf powder has caused product variability, limiting consistency, competitiveness, and industrial use. This study developed quality criteria using the FACTS framework, integrating stakeholder priorities (via Exponential Comparison Method across 24 participants) with laboratory characterization of samples from five Indonesian regions. Stakeholders prioritized food safety, sensory quality, and nutritional consistency. However, food safety parameters were excluded as they are already regulated by Indonesian Food and Drug Authority (BPOM). Laboratory data revealed high variability in fineness (CV = 28.83%) and acid-insoluble ash (CV = 52.67%). Benchmarking against Kenya Standard KS 2848:2019 confirmed compliance for moisture and acid-insoluble ash, while fineness, ash, protein, and color required local specifications. Using Adopt–Adapt–Originate, acid insoluble ash was adopted (≤ 0.5%); moisture and fineness adapted; and ash, protein, and color originated. Stakeholder expectations (protein ≥ 27%; moisture ≤ 8%) exceeded empirical thresholds (≥ 23%; ≤ 10%), resolved through inclusive limits supporting a future tiered system. Proposed specifications, i.e. color (green to bright green), moisture (≤ 10%), ash (≤ 13%), acid-insoluble ash (≤ 0.5%), protein (≥ 23%), and fineness (≥ 80% passing 100-mesh) provide a scientific foundation for moringa powder standard in national level.